Diagnosis and management of chagasic cardiomyopathy patients in several institutions in Argentina - Chuit, Roberto; Antonietti, Laura; Agüero, Roberto Nicolás; Varela, Gabriela Badino; Mordini, Oscar Daniel; Alemandri, Emilce; Abril, Marcelo; Días, Miguel; Yadón, Zaida E.; Pizzi, Hugo; Pizzi, Rogelio (Frontiers in Parasitology, 2023)
Introduction According to estimates by the World Health Organization, the infection and disease caused by the protozoan parasite Trypanosoma cruzi affects almost 6 million people, and more than 1 million suffer chagasic cardiomyopathy (Ch-CMP). It is estimated that 376,000 of these individuals live in Argentina. This study describes the characteristics and medical management of individuals with Ch-CMP in Argentina. Methods This is a descriptive, retrospective, cross-sectional study on the diagnosis and clinical and therapeutic evaluation of patients with Ch-MCP using historical records collected from different medical institutions in the country between 1 January 2018 and 30 June 2021. Results During this period, 652 patients (mean age 61.2 years ± 12.9) were included, with women accounting for 60.3% of the sample. The diagnosis of cardiac insufficiency was 36.0% and 64.4% had arrhythmias. The most common cardiovascular risk factors detected were arterial hypertension (69.5%), smoking (56.6%), and diabetes (20.9%). Less than half of the subjects (45.4%) had been studied by electrocardiogram (ECG), chest X-ray, and echocardiogram. ECG studies showed conduction disorders (38.8%), left ventricular hypertrophy (28.1%), ventricular extrasystoles (22.0%), complete right bundle branch block (8.6%), and atrioventricular block (2.6%). According to the Kuschnir classification, 21.4% of the study subjects were in Grade 3. Conclusions The patients included in the study had a similar clinical presentation and history of the disease to those published in other studies. When evaluating the medical practices, we found that patients were inadequately studied. Although it is difficult to estimate the fraction of the total number of patients represented by the present study, the study allowed us to establish that the care received by patients was not adequate.